ANALISIS KEKERASAN VERBAL DALAM VIDEO YOUTUBE TIMUR KOTA AMBONAI “ PT. LOLANG PENNI”(KAJIAN SEMIOTIKA) - Anugrah, Aldan; Muh. Safar; Muhammad Idris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the forms of verbal violence and the meanings of harsh words found in the YouTube video Ambo Nai "PT. Lolang Penni." The research method used is a qualitative descriptive approach with Ferdinand de Saussure's semiotic analysis, focusing on the relationship between the signifier (signifiant) and the signified (signifié). Data collection was conducted through video transcription, followed by analysis to identify elements of verbal violence based on cultural and social contexts. The research findings show that the video contains various forms of verbal violence, both direct and indirect, such as insults, mockery, threats, and degradation of gender and personal identity. The semiotic analysis reveals that each utterance of verbal violence carries deep meaning that not only represents individual expression but also reflects the social structure, culture, and power relations in the speaker's community.